Frontiers in Gynecological Endocrinology : Volume 2: From Basic Science to Clinical Application - Fauser, Bart C. J. M.; Genazzani, Andrea R. (ISGE Series,, 2015)
This volume offers an up-to-date overview on the major areas of gynecological endocrinology, presenting the latest advances in adolescent gynecological endocrinology, assisted reproduction, menstrual-related disorders, sexuality and transsexualism, polycystic ovary syndrome, myometrial pathology and adenomyosis, obesity and metabolic syndrome, hormonal contraception, premature ovarian failure and menopause. In each chapter the recent advances deriving from basic science and clinical investigations are related to the practical management of the condition under consideration, taking into account the need for individualized therapies. The book is published within the ISGE Book Series, a joint venture between the International Society of Gynecological Endocrinology and Springer and is based on the 2014 International School of Gynecological and Reproductive Endocrinology Winter Course. It will be an important tool for obstetricians and gynecologists, endocrinologists and experts in women's health as well as interested GPs.